FUNDAMENTALS OF THE SCIENCE PHILOSOPHY - Ahmad ANAS; Ahmad ZAYADI; MUHLISIN (Annals of the University of Craiova for Journalism, Communication and Management)
This study aims to examine the fundamentals of the science philosophy from ancient Greece to Islamic philosophy in a comprehensive and in-depth manner. The type of research used in this research is library research. This research is a descriptive research, because it focuses on a systematic explanation of the facts obtained during the literature and literature review. Researchers used content analysis techniques. Because this research discusses in depth the content of written or printed information in books, journals, and mass media as well as other relevant library materials. This research study concludes that the philosophy of science is a branch of philosophical knowledge that examines the differences in the characteristics of the types of science from one another and the various procedures that must be carried out scientifically and what must be done in obtaining a scientific explanation and whether the theory can be applied, taken as a concept. There are three basics of philosophy of science in Ancient Greece, namely, ontology, epistemology and axiology. The ontology of Islamic science can be concluded that the object of science in the view of Islam includes something material and non-material, phenomena and non-phenomena, and there are even forms that, let alone seen, are known to humans. The unseen form whose details are not known is also the object of study of the Islamic sciences. In the perspective of Islamic epistemology, the sources of knowledge consist of the Qur’an, hadith, the five senses and reason. In the perspective of Islamic axiology, the purpose of science is to know the Creator and submit to Allah.